P.1.16 Physical health of transitioned adf and regular adf members in 2015: findings from the transition and wellbeing research programme. (April 2019) - Kelsall, Helen; Hooff, Miranda Van; Lawrence-Wood, Ellie; McFarlane, Alexander; Hodson, Stephanie; Sadler, Nicole; Benassi, Helen; Hansen, Craig; Sim, Malcolm
Abstract : Introduction: Military service can involve exposure to physical and psychological stressors. There has been little systematic research into the health and wellbeing of military personnel after they leave the services. Methods: 4326 Transitioned ADF (transitioned from regular Australian Defence Force service between Jan 2010–Dec 2014) (18% response) and 8480 Regular 2015 ADF (42%) completed a questionnaire including symptoms, doctor-diagnosed medical conditions, respiratory health, injuries, pain, sleep problems, lifestyle factors, self-perceived health and quality of life and health service use. Results: Transitioned ADF reported a higher mean number of symptoms (16.4 vs 11.8), similar mean number of medical conditions (1.9 vs 1.5), were more likely to report some medical conditions (a circulatory, musculoskeletal/connective tissue or nervous system condition, high blood pressure, chronic low back pain, and hearing loss), a slightly higher mean number of service-related injury types (1.11 vs 0.96), and poorer self-perceived health and quality of life compared to 2015 Regular ADF. Service-related injuries were more likely to have been sustained during training than on deployment in both groups. The majority of Transitioned ADF and 2015 Regular ADF reported experiencing some pain intensity and disability. In Transitioned ADF, poorer physical health outcomes overall were reported in Department of Veterans' Affairs (DVA) clients compared with non-DVA clients, in Ex-Serving compared with Active Reservists or Inactive Reservists, and in those who had been medically discharged compared with those discharged for other reasons. Conclusion: This was one of the first studies internationally to investigate a comprehensive range of physical health indicators in recently transitioned military personnel. Overall Transitioned ADF were more likely to report poorer physical health across domains, some subgroups appeared particularly at risk. Findings in DVA clients were consistent with DVA being the conduit for care in veterans who have a service-related injury or mental health condition.